A New way of reliving the school. An analysis conducted in the "Asilo nel Bosco" in Ostia Antica - Zbigniew Szczepan Formella; Giorgia Perillo (The Francis de Sales Scientific Society (TNFS.PL), 2022)
This contribution is a kind of continuum of the previous paper, published in 2/2018 issue. The article is divided into three parts: the first contains a presentation of the "Asilo nel Bosco" of Ostia Antica (Kindergarten in the Forest), which draws upon the Outdoor Education model. The second part, in turn, presents the findings of an exploratory investigation conducted in this educational organization with the aim of verifying and highlighting the strengths of the methodology of Outdoor Education applied in the experience. Finally, the third part examines both the psychophysical benefits of outdoor education and the socio-cultural challenges to which schools in the forest are exposed in the Italian context. Contribution of many educators of the past, such as J. J. Rousseau, M. Montessori, R. Steiner and P. Freire, are tangibly re-emerging in schools in the woods in Italy, in Europe and around the world, creating one of the most precious opportunities for healthy development of the child.